(untitled) (Scientific journal of the Fergana State University, 2026)
The article discusses the methods of developing sociocultural competence through working with poetic literary texts in English. The author substantiates the relevance of developing this competence and provides its theoretical characterization within the framework of the competency-based approach. In addition, the structural components of sociocultural competence are identified, and the main directions and effective pedagogical strategies for its formation are highlighted.